Development of cephalometric radiography in orthodontic imaging: a literature review - Prativi, Shinta Amini; Suksmono, Andriyan Bayu; Mengko, Tati Latifah; Danudirdjo, Donny (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This review article aims to discuss the development of lateral cephalometric radiography use in science until now. Review: The search for studies on the identification of lateral cephalometric anatomical landmarks based on artificial intelligence was conducted by involving four databases: PubMed, IEEE Xplore, Google Scholar, and Scopus. The article selection was conducted using the keywords